Efektivitas Electrical Nerve Stimulation (TENS) Yang Dipadukan Dengan Latihan Peregangan Pada Pasien Low Back Pain: Literatur Review - Khuzaeva Aulia Febriyani; Dini Nur Alpiah (CV. KAMPUS AKADEMIK PUBLISING, 2026)
Low back pain, also called LBP, is a very common issue that affects people who do a lot of standing or lifting work. One way to treat it without surgery is called TENS, which stands for Transcutaneous Electrical Nerve Stimulation. This treatment uses small electrical impulses to help block pain signals in the body, based on the gate control theory of how pain works.When TENS is used along with stretching exercises, it helps even more with reducing pain and improving movement and function. This research is a review of existing studies. The search looked through PubMed, ScienceDirect, and Google Scholar for studies published in the last five years. The studies had to be randomized controlled trials, or RCTs, which are a strong type of study. The results show that using TENS and stretching together helps a lot with reducing pain, making the lower back more flexible, improving range of motion, and helping people feel less disabled. Most of the studies had results that were statistically significant, with p values less than 0.05. Using TENS for 20 to 30 minutes, about 3 to 5 times a week, and doing stretching exercises for 4 to 6 weeks, gives the best results for people with So, putting together TENS and stretching is a good way to help reduce pain and make it easier for people to do daily activities.